2008 Global Financial Crisis Whose Responsibility? - Sanabria González, Jorge Edisson (Universidad Pedagógica y Tecnológica de Colombia, 2011)
An attempt is made to evaluate the responsibility of some financial and multilateral institutions, as well as the responsibility of the United States government, in the financial crisis of 2008. It is important to also review why, despite being warned by many world-renowned economists as the case of Nou rielRoubini or Joseph Stiglitz, about a possible financial crisis, neither the governments nor the International Monetary Fund (IMF), took action on the matter.